5-YEAR EXPERIENCE OF ORTHOTOPIC HEART TRANSPLANTATION IN THE KRASNODAR REGION - K. O. Barbukhatti; E. D. Kosmacheva; M. V. Kolodina; S. Yu. Boldirev; S. A. Belash; I. I. Yakuba; A. A. Skopets; V. A. Porkhanov (Вестник трансплантологии и искусственных органов)
.